Richness in Functional Connectivity Depends on the Neuronal Integrity within the Posterior Cingulate Cortex - Lord, Anton R.; Li, Meng; Demenescu, Liliana R.; van den Meer, Johan; Borchardt, Viola; Krause, Anna Linda; Heinze, Hans-Jochen; Breakspear, Michael; Walter, Martin (Frontiers in Neuroscience, 2017)
The brain’s connectivity skeleton – a rich club of strongly interconnected members - was initially shown to exist in human structural networks, but recent evidence suggests a functional counterpart. This rich club typically includes key regions (or hubs) from multiple canonical networks, reducing the cost of inter-network communication. The posterior cingulate cortex (PCC), a hub node embedded within the default mode network, is known to facilitate communication between brain networks and is a key member of the ‘rich club’. Here, we assessed how metabolic signatures of neuronal integrity and cortical thickness influence the global extent of a functional rich club. Rich club estimation was performed on functional connectivity of resting state brain signals acquired at 3T in 48 healthy adult subjects. Magnetic resonance spectroscopy was measured in the same session using a point resolved spectroscopy sequence. We confirmed convergence of functional rich club with a previously established structural rich club. N-acetyl aspartate (NAA) in the PCC is significantly correlated with age (p=0.001), while the rich club coefficient showed no effect of age (p=0.106). In addition, we found a significant quadratic relationship between RCC and NCC concentration in PCC (p=0.009). Furthermore, cortical thinning in the PCC was correlated with a reduced rich club coefficient after accounting for age and NAA. In conclusion, we found that the rich club is related to a marker of neuronal integrity in a key region of the cingulate cortex. Furthermore, cortical thinning in the same area was observed, suggesting that both cortical thinning and neuronal integrity in the hub regions influence functional integration of at a whole brain level.